Arm-leg coordination in flat breaststroke: A comparative study between elite and non-elite swimmers - Leblanc, H.; Seifert, L.; Baudry, L.; Chollet, D. (International Journal of Sports Medicine, 2005)
The aim of this study was to compare the arm-leg coordination in flat breaststroke among four groups of swimmers (elite males, elite females and non-elite males, non-elite females) of two different competitive levels. Using a velocity-video system, both forward acceleration and deceleration phases of the hip were first identified. Based on these phases, four temporal gaps indicated the time duration between arm and leg actions throughout three race paces (200, 100, and 50 m). For both groups, a velocity increase was combined with an increase of stroke rate, a decrease of stroke length, and an increase of the propulsive phases and a decrease of the glide phases. However, when the relative duration of one stroke cycle was considered, the elite swimmers had significant shorter time of the glide phase than lower competitive level swimmers (18.80 % vs. 31.04 % for females and 11.89 % vs. 19.60 % for males) combined with a longer stroke length (respectively 2.05 m vs. 1.73 m and 2.03 m vs. 1.82 m). Furthermore, the temporal gaps of the elite swimmers showed a greater continuity in the arm and leg actions, which indicates a better timing than non-elite swimmers. It was concluded that elite breaststroke swimmers are able to optimise their propulsion by reducing their glide phase and using a more continuous timing between arm and leg coordination.